ONLINE CONSUMPTION BEHAVIOUR DURING COVID-19 PANDEMIC IN MALAYSIA - Y. L. Adeline Tam; Tung Moi Chiew (International Journal of Accounting, Finance and Business, 2022)
Due to the COVID-19 outbreak in Malaysia in March 2020, the Malaysian government announced Movement Control Order (MCO) from 18th March 2020. In line with the stay-at-home policies, Malaysian residents were encouraged to purchase household essentials online and use cashless payment. Study was conducted to study the changes in online consumption behaviour among Malaysian residents during the pandemic. This article focuses on reporting facts and figures on the purchase of food and household essentials among Malaysian residents. An online survey questionnaire was distributed online. Data collected was analysed with descriptive statistics. Findings confirmed that respondents who seldom or never bought online reduced tremendously during the MCO period. Most respondents reported that they will continue to purchase online after MCO lifted although at a lower frequency. Cooked food and telecommunication products were the most frequently bought products. FoodPanda, Grab Food, and Shopee platforms were popular platforms used for online purchases. Although e-payment method was popular, cash remained a popular mode of payment. Social media was a very important source of information for the online purchase. This study contributed to the understanding of consumer online consumption behaviour and provided information to examine further factors that influenced the changes in online consumption behaviour.